Schooling as a Vehicle for Aboriginal Language Maintenance: Implementing Cree as the Language of Instruction in Northern Quebec - McAlpine, Lynn; Herodier, Daisy (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
(Cree translation by Ethel Blackned) Aboriginal languages in Canada are at risk. Aboriginal communities that control their own schools often perceive schooling as a means of halting the erosion of language and restor- ing the viability of their culture. This is the story of such a process. The James Bay Cree live in nine communities, mostly along the east coast of James Bay. In December 1988, the Cree School Board commissioners decided to introduce a program of Cree as the lan- guage of instruction in elementary schools. We describe the development of the project (now in the initial stage of implementation) and analyze its strengths and weaknesses. Al- though this program’s ultimate impact on the preservation of Cree language (and culture) cannot yet be known, it is clear that the community plays an important role in creating and sustaining the motivation for the change. Les langues autochtones au Canada sont en péril. Les communautés autochtones qui gèrent leurs propres écoles voient dans celles-ci un moyen de mettre fin à l’érosion de leur langue et de restaurer la viabilité de leur culture. L’article illustre ce processus. Les Cris de la Baie James vivent dans neuf villages situés pour la plupart le long de la côte est de la Baie James. En décembre 1988, les commissaires de la Commission scolaire crie ont décidé de mettre en oeuvre un programme axé sur le cri comme langue d’enseigne- ment dans les écoles primaires. Les auteures décrivent le processus d’élaboration de ce projet (actuellement à la phase initiale de son implantation) et analysent ses forces et ses faiblesses. Bien que l’impact final de ce programme du point de vue de la préservation de la langue et de la culture cries ne soit pas encore connu, il est clair que la communauté joue un rôle important dans la volonté de créer et de maintenir ce changement.